Assessment of growth among children with type 1 diabetes mellitus - Pavadigoudra, Mallanagouda Kuberagouda; Sajjanar, Sujata B.; K., Uday; B., Ushakiran C. (International Journal of Contemporary Pediatrics, 2024)
Background: As insulin is important regulator of growth hormone related factors, especially insulin like growth factors (IGF-1) and insulin like growth factors binding proteins (IGFBP-3), disorders of insulin production can result in poor growth. Studies suggest that growth abnormalities are common in subjects with poor metabolic control and longer disease duration. Growth parameters are important indicators of a child overall health and they are influenced by factors like blood glucose control in diabetic children. Methods: After obtaining institutional ethical committee clearance and informed consent from parents/subjects, a prospective observational study was conducted from January 2018 to June 2019. Anthropometry of each participant (height, weight, BMI) measured and 4 ml of venous blood was collected for HbA1C levels. Results were compared with age specific standards. Anthropometry and blood investigations performed once in 3 months for 1 year. Results: Out of 30 cases, 53.3% (n=16) were males and 46.7% (n=14) were females with M:F ratio of was 1:1.04. Among those with poor HbA1C control 73.69% (n=14) had short stature at the entry of the study and the results was statistically significant (p=0.043). Among those with poor HbA1C control, 72.73% (n=08) had short stature at the one year follow up and the results was statistically significant (p=0.017). Which suggests that linear growth in children with type 1 diabetes is highly related to glycemic control. Conclusions: Growth was compromised in diabetic children. Children diagnosed at younger age need monitoring of good glycemic control and drug compliance to optimize the growth.